Ameloblastoma, Human Papillomavirus, and p16- is there An Association? - Thasvir Singh; Christopher Angel; Sepehr Tabrizi; Alyssa Cornall; John Clement; Arun Chandu (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Background: The aetiology of the ameloblastoma is still unclear. Several studies have searched for the presence of human papillomavirus (HPV) in ameloblastomas, however the results have been mixed. Our aim is to clarify this possible association, and to determine if p16 is a reliable surrogate marker for the presence of HPV in these tumours.  Methods: Forty-one cases of ameloblastoma and 1 ameloblastic carcinoma were identified and underwent immunohistochemical (IHC) testing for p16 and polymerase chain reaction (PCR) testing to detect HPV DNA. Results: 80.5% of the benign ameloblastomas were 'overall positive' for p16 (56.1% strong positive, and 24.4% moderately positive) and 19.5% 'overall negative'. The single case of ameloblastic carcinoma also stained strongly positive for p16. PCR did not detect HPV DNA in any of the 42 cases.   Conclusions: We did not find any positive HPV ameloblastomas within the samples evaluated. Despite most ameloblastomas being p16-positive, p16 cannot be used as a marker of HPV within these tumours.